Information Technology as an Enabler of Growth in Firms: An Empirical Assessment - MITRA, SABYASACHI (Journal of Management Information Systems, 2005)
This research provides empirical evidence of the role of information technology (IT) as an enabler of growth in firms. We postulate that as a firm grows larger, a superior IT infrastructure increases the productivity of other inputs by controlling the complexity-related costs that the firm incurs as it increases in size. In the empirical analysis to support this view, we find that firms with high-growth expectations increase their IT spending as their free cash flow increases, whereas low-growth firms maintain a constant level of IT spending, irrespective of their free cash flow. Further, we analyze the effect of IT investments in one period on growth-related metrics in subsequent periods. We find that a superior IT infrastructure significantly reduces the cost of operations for high-growth firms in subsequent periods. In summary, the theory and empirical evidence presented in this paper point to an indirect but important contribution of the IT infrastructure to a firm's growth.